Os programas sociais de educação integral sob a ótica da Constituição da República de 1988 e da Declaração de Jomtien de 1990 - NICARETTA, Cendy Castro (Universidade Federal do Oeste do Pará, 2024)
In this study, it starts from the central theme Integral Education, to address the theme Social Policies for Integral Education and analyze Social Programs for Integral Education of the Federal Executive Power of Brazil, object studied from the normative actions: Mais Educação Program (MEP), Novo Mais Educação Program (NMEP) and Ensino Médio Inovador Program (EMIP). The guiding question of this research was to know whether such regulations follow the basic principles for fundamental or comprehensive education provided for in the 1990 Jomtien Declaration and the 1988 Constitution of the Brazilian Republic (CBR/1988). Thus, the main objective of this study was to analyze whether the normative actions of the Federal Executive Power, which established the PME, PNME and ProEMI, fit the assumptions of comprehensive education provided for in the 1990 Jomtien Declaration and in the CBR/1988. And the specific objectives were: to analyze the assumptions of the public policy of integral education; raise the norms that recognize, protect and implement the public policy of integral education; and to verify if the social programs of integral education, proposed by the Federal Executive Power, follow the precepts verified in the CBR/1988 and in the Declaration of Jomtien of 1990 on the right to integral education. For the development of the work, the hermeneutic method of content analysis was adopted, considering it more appropriate to the nature of the research. A qualitative bibliographic and documentary approach was used, which served as the basis for data collection, interpretation and systematization of the collected information to outline the results of the investigation. Among the results, it was noticed that the normative actions of the Federal Executive Power, between 2007 and 2016, followed the assumptions of integral education, or the right to full training of subjects, described in the 1990 Jomtien Declaration and in the CBR/1988. In 2016, with the reform of the MEP to the NMEP, it can be said that there was an indication of a setback in the analyzed public policies. It was concluded that the social policy of comprehensive education needs to be a State policy, as the 1990 Jomtien Declaration reiterates: for an effective change in the quality of education in a country, the State and society need to develop public policies for short-term results, medium and long term. And it is for this reason that I see the urgency of a social and political pact.